New Economy, Old Central Banks? - Jan Marc Berk (Tinbergen Institute, 2002)
Proponents of the so-called New Economy claim that it entails a structural change of the economy. Such a change, in turn, would require the central bank to rethink its monetary policy to the extent that traditional relationships between inf1ation and economic growth are no longer valid. But such a rethinking presupposes that prospective advances in information technology and other factors associated with the new economy do not threaten the capacity of central banks to stabilise the general level of prices. It is the aim of this paper to shed some light on the latter, by analysing the monetary transmission mechanism in a 'new economy' environment. We argue that, although the form of central bank instruments and current methods for implementing monetary policy may change, the goals that the policy makers try to achieve by employing these instruments remain valid, and achievable.
Keywords: E51; E52; E58; 330; Electronic money; New Economy; Monetary policy; Geldpolitische Transmission; Elektronisches Geld; Bargeldloser Zahlungsverkehr; Geldpolitik; Welt; New Economy